Least mean sixth control approach for three-phase three-wire grid-integrated PV system - Touheed Khan; Mohammed Asim; Mohammad Saood Manzar; Md Ibrahim; Shaikh Sadaf Afzal Ahmed (Institute of Advanced Engineering and Science, 2021)
This work proposes an adaptive filter based on a new least mean sixth control approach with incremental conductance method of MPP for 3-phase grid-incorporated photovoltaic (PV) system. The proposed system comprises a PV array, 3-phase DC to AC converter, maximum power point tracker (MPPT), three-phase electronic load, and a 3-phase grid. The combination of solar PV array and the voltage source converter (VSC) supplies power to the grid. The 3-phase inverter as a distribution static synchronous compensator (D-STATCOM) improves the quality of the system performance in case of zero solar irradiation. D-STATCOM also reduces total harmonic distortion (THD) in grid currents, improves power factor, and maintainsa constant voltage at the point of common coupling (PCC). The system modelling and simulation is achieved on MATLAB/Simulink. The proposed system performance has been found satisfactory and conform to IEEE-519 standards.